Automation in the drying process paprika (capsicum annuum) with solar energy - Sergio Orlando Mestas Ramos (2019)
Paprika’s export requires optimization in terms of drying, to be competitive. The research achieved the construction of a commercial dryer 25 0kg and 1000 kg industrial, after experiencing different conditions without exceeding temperatures that can damage the labile elements, We can provide information on the importance of automation in the process of drying paprika export in Arequipa region through the accumulation of solar energy in solar collectors industrial dryers paprika. The determining parameters of the process are speed, temperature and relative humidity, moisture product also sun light, while commissioning of centrifugal fans, down time for centrifugal fans proper control and optimization in the drying process. The results were cut losses capsinas carotenoids and 10% and reduce the cost of drying 0.9 kg of dried soles pepper exportersincreasing income.